2021
DOI: 10.1111/tri.13982
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Epstein–Barr virus reactivation after renal transplantation: Results of a large, multi‐centre study

Abstract: Summary Epstein–Barr virus (EBV) reactivation is a very common and potentially lethal complication of renal transplantation. However, its risk factors and effects on transplant outcome are not well known. Here, we have analysed a large, multi‐centre cohort (N = 512) in which 18.4% of the patients experienced EBV reactivation during the first post‐transplant year. The patients were characterized pre‐transplant and two weeks post‐transplant by a multi‐level biomarker panel. EBV reactivation was episodic for most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
6
2
Order By: Relevance
“…We found the highest proportion of EBV DNAemia in subjects who were D+/R− at time of transplant (37.5%) compared with rates of 3.5% and 0% in the R+ and D−/R− groups, respectively. The overall rate of EBV DNAemia in this study is lower than in previous reports in adult SOT recipients (13–67%) [ 6 , 8 10 , 24 26 ]. Most recently, Blazquez-Navarro et al observed 18.4% of patients in a multicenter cohort experienced EBV reactivation in the first posttransplant year [ 6 ].…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…We found the highest proportion of EBV DNAemia in subjects who were D+/R− at time of transplant (37.5%) compared with rates of 3.5% and 0% in the R+ and D−/R− groups, respectively. The overall rate of EBV DNAemia in this study is lower than in previous reports in adult SOT recipients (13–67%) [ 6 , 8 10 , 24 26 ]. Most recently, Blazquez-Navarro et al observed 18.4% of patients in a multicenter cohort experienced EBV reactivation in the first posttransplant year [ 6 ].…”
Section: Discussioncontrasting
confidence: 87%
“…The overall rate of EBV DNAemia in this study is lower than in previous reports in adult SOT recipients (13–67%) [ 6 , 8 10 , 24 26 ]. Most recently, Blazquez-Navarro et al observed 18.4% of patients in a multicenter cohort experienced EBV reactivation in the first posttransplant year [ 6 ]. The infrequent screening in our cohort may have led to underestimation of rates of EBV DNAemia.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations